1992
DOI: 10.1177/172460089200700207
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/Neu Gene in Primary and Local Metastatic Axillary Lymph Nodes in Human Breast Tumors

Abstract: In order to verify whether the HER-2/neu gene is involved in the initial phases of neoplastic disease or in its progression, we evaluated the amplification and overexpression of this gene in the primary tumor and in synchronous metastatic axillary lymph nodes of 26 women with operable breast cancer. HER-2/neu was amplified in 35% and overexpressed in 33% of the primary sites; similar percentages were found in lymph nodes. The clear correlation between the two disease sites regarding gene, mRNA and protein leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Comparisons of primary cancers and their lymph node metastases have shown that they are similar phenotypically, as defined by their histology, proliferation (Feichter et al, 1989;Daidone et al, 1990;Goodson et al, 1993), and oncogene expression (Moffett et al, 1992;Tommasi et al, 1992). On the other hand, acquisition of some abnormalities during metastasis of human solid tumors, including an increased expression level of epidermal growth factor receptor (EGFR) (Mori et al, 1991) and focal adhesion kinase mRNA (Weiner, 1993) in breast cancer, reduction of E-cadherin expression in squamous cell carcinoma of the head and neck (Behrens et al, 1993), and mutations in p16INK4 and p15INK4B genes in non-small cell lung cancer (Okamoto et al, 1995) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of primary cancers and their lymph node metastases have shown that they are similar phenotypically, as defined by their histology, proliferation (Feichter et al, 1989;Daidone et al, 1990;Goodson et al, 1993), and oncogene expression (Moffett et al, 1992;Tommasi et al, 1992). On the other hand, acquisition of some abnormalities during metastasis of human solid tumors, including an increased expression level of epidermal growth factor receptor (EGFR) (Mori et al, 1991) and focal adhesion kinase mRNA (Weiner, 1993) in breast cancer, reduction of E-cadherin expression in squamous cell carcinoma of the head and neck (Behrens et al, 1993), and mutations in p16INK4 and p15INK4B genes in non-small cell lung cancer (Okamoto et al, 1995) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies in the literature have focused on the metastasic lesions associated with human carcinomas. With regard to breast cancer, studies on paired primary tumours and metastasic axillary lymph nodes (MALNs) from the same patients have demonstrated that both lesions show similar phenotype in histopathology, proliferation activity (Feichter et al 1989;Daidone et al 1990;Tommasi et al 1992;Chang et al 1993;Goodson et al 1993) oestrogen and progesterone receptors (Andersen & Poulsen 1988;van Agthoven et al 1995;Umekita et al 1998), and oncogene expression (Moffett et al 1992;Tommasi et al 1992). However, acquired abnormalities in MALNs of breast carcinomas have been described, such as increased levels of epidermal growth factor receptor (Mori et al 1991) or heat shock protein 27 over-expression (Storm et al 1996), and these genetic alterations are present with higher frequency in the metastatic areas than in primary breast carcinomas (Nishizaki et al 1997).…”
mentioning
confidence: 99%
“…Από την άλλη, περίπου 30% των όγκων που είναι αρνητικοί ως προς τους λεμφαδένες επανέρχονται μετά από 5 χρόνια. Η ερώτηση που προκύπτει είναι αν η υπερέκφραση της πολυμεράσης συνδέεται ή προσδίδει βιολογικά χαρακτηριστικά στους όγκους που τους κάνει περισσότερο επιθετικούς Με τα μέχρι σήμερα δεδομένα, συγκριτική μελέτη πρωτογενών όγκων και μεταστάσεων στους λεμφαδένες έδειξε ότι είναι παρόμοιοι φαινοτυπικά, όπως ορίζεται από την ιστολογία, τον πολλαπλασιασμό (317)(318)(319) και έκφραση ογκογονιδίων (320,321). Από την άλλη έχει αναφερθεί εμφάνιση κάποιων επιπλέον ανωμαλιών σε δευτερογενείς στερεούς όγκους, όπως αυξημένα επίπεδα έκφρασης του επιδερμικού παράγοντα αύξησης (EGFR) (322) και του ειδικού mRNA της κινάσης συνοχής (323) στον καρκίνο του μαστού, μείωση της έκφρασης της καντερίνης Ε στο σκηρρώδες καρκίνωμα της κεφαλής και του λαιμού (324) και μεταλλάξεις των ρ16ΙΝΚ4 και pi 5ΓΝΚ4Β γονιδίων στον καρκίνο του πνεύμονα (325) high mitotic index and without oestrogen receptors had more genetic changes than the others.…”
Section: 2β επιμέρους γενετικές ανωμα/ίες και κήνικοπαθολογικοίχαρακτήρεςunclassified